Soil Quality Indicators under Different Smallholder Managed Cropping and Landuse Practices in Abuja, Nigeria - Safirat Sani; Sani Abubakar Mashi; Clement Didi Chup (MO.RI Publishing, 2023)
There are limited reports about the impacts of smallholder-managed cropping and land-use practices (CLUPs) on soil quality, especially in developing countries. This study investigates the impact of six different Cropping Land Use Practices (CLUPs) on soil quality parameters in Abuja, Nigeria, focusing on sesame mono-cropping (SM), guinea corn mono-cropping (GCM), yam mono-cropping (YM), maize + yam mixed cropping (MYM), maize mono-cropping (MM), and natural forest (NF). The objectives are to determine Soil Organic Carbon (SOC), Total Nitrogen (TN), and pH values in the six CLUPs and assess differences under various CLUPs and soil depths. The study conducted in the University of Abuja Permanent Site, covers 11,000 hectares and analyzes soil samples from three replicate plots per CLUP, considering topsoil (0-15cm) and subsoil (20-30cm). The results indicate slightly acidic soils with low SOC and TN contents. Significant differences in SOC, TN, and C/N ratio are observed among cropping systems, with mixed cropping (MYM) promoting higher SOC. The C/N ratio is consistently low across CLUPs, indicating accelerated decomposition. While intra-plot soil heterogeneity is low, significant declines in soil quality indicators are noted under cropping systems compared to the natural forest. The study recommends site-specific, sustainable land management practices tailored to each cropping system. Encouraging organic matter additions, such as using animal and farmyard manure, is proposed to enhance soil fertility and reverse degradation trends. The findings contribute to understanding how diverse cropping practices impact soil quality, providing valuable insights for sustainable land management in the Abuja region.